Republicanism as valorative component of collective intelligence oriented for social control: limits and possibilities - Pires, Valdemir [UNESP] (Univ Castilla-la Mancha, Fac Ciencias Juridicas & Sociales, 2016)
This paper discusses the different understandings about social control and accountability mechanisms, from the perspectives of neo-republicanism and economic theory of democracy (public choice). Seeks to identify the possibility of advancing a valorative component of republican nature of this control, taking into account the recent achievements in the field of information technology, especially the consolidation of the world wide web (internet), with reference to the concept of collective intelligence, by Pierre Levy (1997). Suggests a range of qualitative and normative research on the topic.
Keywords: InternalControl; External Control; Social Control; Republicanism; Collective Intelligence